Antistatic composition and preparation method thereof
By adding conductive fillers and macromolecular antistatic agents to the polyethylene composition, a conductive network is formed, and the problem of electrostatic accumulation of polyethylene composition is solved, and excellent antistatic properties and comprehensive properties are achieved.
Patent Information
- Application Number
- CN202411729878.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During use, polyethylene compositions are prone to vacuuming, electric shock or even explosion due to static electricity accumulation. The existing anti-static modification methods are ineffective and costly.
An antistatic composition is adopted, which includes high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, conductive fillers, carbon black and macromolecular antistatic agents, and is prepared by melt blending to form a conductive network to reduce surface resistivity.
The antistatic and comprehensive properties of the polyethylene composition are significantly improved, the risk of electrostatic accumulation is reduced, and the wear resistance is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antistatic compositions, and in particular to an antistatic composition and a preparation method thereof. Background Art
[0002] Polyethylene compositions have the advantages of high cost performance, good mechanical properties, stable thermal properties, excellent processing properties and electrical insulation properties, and are widely used in various fields such as industry, agriculture, medical care, scientific research and daily life. However, their surface conductivity is poor. During use, static electricity is easily accumulated on the surface of the product due to friction, extrusion and other reasons, causing dust absorption, electric shock, and even sparks leading to explosions and other malignant accidents. In order to avoid such accidents, plastic products must be treated with antistatic treatment in some occasions.
[0003] Traditional polyethylene compositions are often modified for antistatic properties by adding antistatic agents or adding more conductive fillers. Ordinary antistatic agents will migrate, and the antistatic effect will decrease or disappear over time. High-molecular permanent antistatic agents are expensive, and the amount added is large, the cost is high, the effect is not outstanding, and the application range is narrow. Adding fillers, such as conductive carbon black, has a better effect, but the disadvantage is that the dispersion effect is poor and the processability is not very good. Therefore, it is necessary to develop a polyethylene composition with good comprehensive performance and excellent antistatic performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an antistatic composition and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antistatic composition comprises the following raw materials in parts by weight: 30-40 parts of high-density polyethylene, 10-20 parts of linear low-density polyethylene, 5-15 parts of metallocene polyethylene, 0.5-3 parts of antioxidant, 3-6 parts of dispersant, 1-3 parts of lubricant, 8-15 parts of conductive filler, 3-5 parts of carbon black, 5-10 parts of macromolecular antistatic agent, and 0.1-0.5 parts of initiator; The conductive filler is prepared by the following steps: Step A1, add 0.1 mol / L 2-aminoterephthalic acid DMF (N, N-dimethylformamide) solution to a mixture of deionized water and ethanol and stir for 10 min, then add 0.075 mol / L copper nitrate DMF solution and 0.075 mol / L nickel nitrate DMF solution and mix evenly, finally add triethylamine and sonicate for 1-2 h, centrifuge, collect precipitate, wash and dry to obtain CuNi-MOF powder; Step A2, dispersing sodium molybdate in deionized water and adjusting the pH to 6.5, then adding L-cysteine aqueous solution for ultrasonic treatment for 10-20 minutes, hydrothermally reacting in an autoclave at 180-200° C. for 24 hours, centrifuging, and collecting the supernatant to obtain MoS2QDs; Step A3, after the CuNi-MOF powder and MoS2 QDs are evenly mixed, ultrasonic treatment is performed for 30 minutes, and then oil bath treatment is performed at 70°C for 5-8 hours. After centrifugation, washing and drying, calcination is performed at 300-400°C for 1-2 hours to obtain a MoS2 QDs / CuNi-MOF composite material; Step A4, 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and deionized water were mixed evenly, and the MoS2 QDs / CuNi-MOF composite material was added and ultrasonically dispersed for 30 minutes, then the temperature was raised to 30°C, dopamine hydrochloride was added and stirred for reaction for 8-12 hours, centrifuged, washed, and dried to obtain a conductive filler; Further, in step A1, the volume ratio of 2-aminoterephthalic acid DMF solution, deionized water, ethanol, copper nitrate DMF solution, nickel nitrate DMF solution and triethylamine is 15:1:1:5-8:2-5:1.5; Further, in step A2, the dosage ratio of sodium molybdate, deionized water and L-cysteine aqueous solution is 0.2-0.5 g: 50 mL: 40-60 mL, and the L-cysteine aqueous solution is prepared by mixing L-cysteine and deionized water in a dosage ratio of 0.5-1.2 g: 40-60 mL; Further, in step A3, the ratio of CuNi-MOF powder to MoS2 QDs is 0.1-0.2 g: 50-80 mL; Furthermore, in step A4, the usage ratio of Tris-HCl buffer solution, deionized water, MoS2 QDs / CuNi-MOF composite material and dopamine hydrochloride is 1-2 mL: 100 mL: 0.5-1.5 g: 0.15-0.45 g.
[0006] The macromolecular antistatic agent is prepared by the following steps: Step B1, dispersing tetraethyl orthosilicate and dimethyldiethoxysilane in a mixture of ethanol and deionized water, and stirring for 1-2 hours, then slowly adding 3-butylenetriethoxysilane and continuing stirring for 1-2 hours, adding 10wt% ammonia water and stopping stirring, and transferring to a 60°C water bath and standing for 30-50 minutes, centrifuging, washing, and drying to obtain terminal double-bond organosilicon; Step B2, adding allylamine and triethylamine to dichloromethane, slowly adding dimethyl chlorophosphate at 0-5°C, and stirring for 40-60 minutes, then heating to room temperature and stirring for 8-12 hours, filtering, washing, and drying, that is, the functional monomer; Step B3, uniformly dispersing acrylic acid, functional monomers, and hydroxyethyl methacrylate in ethanol, recorded as a mixed solution; ultrasonically dispersing the double-bond-terminated silicone in ethanol, then sequentially adding the mixed solution and azobisisobutyronitrile ethanol solution, and heating to 55-65° C. to react for 3-5 hours, centrifuging, washing, and drying to obtain a macromolecular antistatic agent; Further, in step B1, the dosage ratio of tetraethyl orthosilicate, dimethyldiethoxysilane, ethanol, deionized water, 3-butenetriethoxysilane and ammonia water is 0.03-0.06 mol: 0.02-0.04 mol: 100 mL: 100 mL: 0.01-0.03 mol: 10 mL; Further, in step B2, the usage ratio of allylamine, triethylamine, dichloromethane and dimethyl chlorophosphate is 0.051-0.153 mol: 0.05-0.15 mol: 200 mL: 0.05-0.15 mol; Furthermore, in step B3, the dosage ratio of the double-bond organosilicon, ethanol, the mixed solution and the azobisisobutyronitrile ethanol solution is 1-2g:100mL:50mL:10mL, the dosage ratio of acrylic acid, functional monomer, hydroxyethyl methacrylate and ethanol in the mixed solution is 0.01-0.03mol:0.05-0.08mol:0.02-0.04mol:50mL, and the azobisisobutyronitrile ethanol solution is prepared by stirring and mixing azobisisobutyronitrile and ethanol in a dosage ratio of 0.1-0.15g:10mL.
[0007] A method for preparing an antistatic composition comprises the following steps: Step S1, weighing raw materials by weight, adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, conductive filler and carbon black into a blender and mixing for 5-10 minutes, then adding antioxidant 1010, dispersant, lubricant, macromolecular antistatic agent and initiator and continuing to mix for 10 minutes to obtain a mixture; Step S2, adding the mixed material into a twin-screw extruder, melt-blending at 190-220° C., extruding, and granulating to obtain an antistatic composition.
[0008] Beneficial effects of the present invention: The antistatic composition in the present application is prepared by melt blending with polyolefin resin as base resin, adding conductive fillers, macromolecular antistatic agents and other functional additives, which not only improves the antistatic properties of the composition, but also improves its comprehensive performance; wherein, the conductive filler forms a conductive network in the matrix through the synergistic effect of MOF, MoS2 QDs and polydopamine, thereby reducing the surface resistivity of the matrix material and further improving the antistatic properties of the matrix; and the macromolecular antistatic agent synergistically improves the antistatic properties of the matrix with the conductive filler and carbon black, and during the melt blending process, the macromolecular antistatic agent can be grafted into the base resin by using an initiator to further improve the antistatic properties and wear resistance of the matrix.
[0009] In the conductive filler, 2-aminoterephthalic acid was first used as an organic ligand, copper nitrate and nickel nitrate were used as copper source and nickel source respectively to synthesize bimetallic CuNi-MOF powder containing amino groups; then sodium molybdate and L-cysteine were used as raw materials to hydrothermally synthesize MoS2 QDs (molybdenum disulfide quantum dots); the quantum dots were then loaded on the surface and void structure of the bimetallic CuNi-MOF, and calcined at high temperature to obtain MoS2 QDs / CuNi-MOF composite materials; finally, dopamine hydrochloride was used to condense on the surface of the composite material to form a polydopamine film, and the polydopamine film adsorbed carbon black to obtain a conductive filler. Conductive fillers use the synergistic effect of carbon black, MOF, MoS2 QDs and polydopamine to form a conductive network in the matrix, thereby reducing the surface resistivity of the matrix material and allowing the accumulated charges inside and on the surface of the matrix to be released quickly, thereby improving the antistatic performance of the matrix; among them, bimetallic MOF has better conductivity than monometallic MOF, because the copper and nickel elements in the bimetallic MOF can work synergistically to form more conductive channels in the MOF structure, thereby reducing resistance and improving the transmission efficiency of electrons, thereby improving the conductivity of the matrix; and loading MoS2 QDs quantum dots, which have excellent conductivity, on the pores and surface of MOF and calcining them at high temperature can further improve the conductive properties of the conductive filler; the formation of the polydopamine film not only improves the dispersibility of the conductive filler in the matrix, but also utilizes the catechol structure with excellent adsorption in polydopamine to evenly "anchor" the conductive filler in the matrix, reducing the migration or aggregation of the filler during the use of the matrix, and further improving the antistatic performance of the matrix. In the macromolecular antistatic agent, tetraethyl orthosilicate, dimethyldiethoxysilane and 3-butenetriethoxysilane are first used as raw materials to synthesize terminal double-bond silicone; then allylamine is reacted with dimethyl chlorophosphate to synthesize functional monomers; finally, azobisisobutyronitrile is used as an initiator to free radical polymerize terminal double-bond silicone, acrylic acid, functional monomers and hydroxyethyl methacrylate to synthesize the macromolecular antistatic agent. The addition of macromolecular antistatic agents can not only synergistically improve the antistatic properties of the matrix with conductive fillers and carbon black, but also can use initiators to graft macromolecular antistatic agents into the matrix resin during melt blending processing, thereby inhibiting the migration of antistatic agents in the matrix. At the same time, the hydrophilic groups (such as phosphate, carboxyl, hydroxyl, etc.) introduced into the macromolecular antistatic agents can adsorb water molecules on the surface of the matrix to form a water film, thereby reducing the surface resistivity of the matrix surface. In addition, the organic silicon structure contained in it also improves the wear resistance of the matrix. This is because the unique microsphere structure of organic silicon can improve the surface smoothness of the polymer matrix, reduce the friction coefficient, thereby reducing wear and improving wear resistance. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0011] The conductive filler is prepared by the following steps: Step A1, adding 0.1 mol / L 2-aminoterephthalic acid DMF solution to a mixture of deionized water and ethanol and stirring for 10 min, then adding 0.075 mol / L copper nitrate DMF solution and 0.075 mol / L nickel nitrate DMF solution and mixing evenly, finally adding triethylamine and ultrasonicating for 1 h, centrifuging, collecting the precipitate, washing, and drying to obtain CuNi-MOF powder, the volume ratio of 2-aminoterephthalic acid DMF solution, deionized water, ethanol, copper nitrate DMF solution, nickel nitrate DMF solution and triethylamine is 15:1:1:5:5:1.5; Step A2, 0.2 g of sodium molybdate was dispersed in 50 mL of deionized water, and the pH was adjusted to 6.5, and then 40 mL of L-cysteine aqueous solution was added and ultrasonically treated for 10 min, and then hydrothermally reacted in an autoclave at 180 ° C for 24 h, centrifuged, and the supernatant was collected to obtain MoS2 QDs. The L-cysteine aqueous solution was prepared by mixing L-cysteine and deionized water in a dosage ratio of 0.5 g: 40 mL; Step A3, after 0.1 g CuNi-MOF powder and 50 mL MoS2 QDs were mixed evenly, ultrasonic treatment was performed for 30 min, and then oil bath treatment was performed at 70°C for 5 h. After centrifugation, washing, and drying, calcination was performed at 300°C for 1 h to obtain a MoS2 QDs / CuNi-MOF composite material; Step A4, mix 1 mL of 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and 100 mL of deionized water, add 0.5 g of MoS2 QDs / CuNi-MOF composite material, ultrasonically disperse for 30 min, then heat to 30 ° C, add 0.15 g of dopamine hydrochloride, stir and react for 8 h, centrifuge, wash and dry to obtain a conductive filler.
[0012] The macromolecular antistatic agent is prepared by the following steps: Step B1, disperse 0.03 mol of tetraethyl orthosilicate and 0.02 mol of dimethyldiethoxysilane in a mixture of 100 mL of ethanol and 100 mL of deionized water, and stir for 1 hour, then slowly add 0.01 mol of 3-butylenetriethoxysilane and continue stirring for 1 hour, add 10 mL of 10 wt% ammonia water and stop stirring, transfer to a 60° C. water bath and let stand for 30 minutes, centrifuge, wash, and dry to obtain terminal double-bond organosilicon; Step B2, add 0.051 mol of allylamine and 0.05 mol of triethylamine into 200 mL of dichloromethane, slowly add 0.05 mol of dimethyl chlorophosphate at 0°C, and stir for 40 min, then heat to room temperature and stir for 8 h, filter, wash and dry, to obtain a functional monomer; Step B3, 0.01mol acrylic acid, 0.05mol functional monomer, 0.02mol hydroxyethyl methacrylate are uniformly dispersed in 50mL ethanol, recorded as a mixed solution; 1g of double-bonded silicone end is ultrasonically dispersed in 100mL ethanol, and then 50mL of the mixed solution and 10mL of azobisisobutyronitrile ethanol solution are added in sequence, and the temperature is raised to 55°C for reaction for 3h, centrifuged, washed, and dried to obtain a macromolecular antistatic agent. The azobisisobutyronitrile ethanol solution is prepared by stirring and mixing azobisisobutyronitrile and ethanol in a dosage ratio of 0.1g:10mL. Example
[0013] The conductive filler is prepared by the following steps: Step A1, adding 0.1 mol / L 2-aminoterephthalic acid DMF (N, N-dimethylformamide) solution to a mixture of deionized water and ethanol and stirring for 10 min, then adding 0.075 mol / L copper nitrate DMF solution and 0.075 mol / L nickel nitrate DMF solution and mixing evenly, finally adding triethylamine and ultrasonicating for 1.5 h, centrifuging, collecting precipitates, washing, and drying to obtain CuNi-MOF powder, the volume ratio of 2-aminoterephthalic acid DMF solution, deionized water, ethanol, copper nitrate DMF solution, nickel nitrate DMF solution and triethylamine is 15:1:1:6:3:1.5; Step A2, dispersing 0.35 g of sodium molybdate in 50 mL of deionized water, adjusting the pH to 6.5, adding 50 mL of L-cysteine aqueous solution, ultrasonically treating for 15 min, hydrothermally reacting in an autoclave at 190 ° C for 24 h, centrifuging, collecting the supernatant, and obtaining MoS2 QDs, wherein the L-cysteine aqueous solution is prepared by mixing L-cysteine and deionized water in a dosage ratio of 0.85 g: 50 mL; Step A3, after 0.15 g CuNi-MOF powder and 65 mL MoS2 QDs were mixed evenly, ultrasonic treatment was performed for 30 min, and then oil bath treatment was performed at 70°C for 6 h. After centrifugation, washing, and drying, calcination was performed at 350°C for 1.5 h to obtain a MoS2 QDs / CuNi-MOF composite material; Step A4, mix 1.5 mL of 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and 100 mL of deionized water, add 1 g of MoS2 QDs / CuNi-MOF composite material, ultrasonically disperse for 30 min, then heat to 30 ° C, add 0.25 g of dopamine hydrochloride, stir and react for 10 h, centrifuge, wash and dry to obtain a conductive filler.
[0014] The macromolecular antistatic agent is prepared by the following steps: Step B1, disperse 0.045 mol of tetraethyl orthosilicate and 0.03 mol of dimethyldiethoxysilane in a mixture of 100 mL of ethanol and 100 mL of deionized water, and stir for 1.5 h, then slowly add 0.02 mol of 3-butylenetriethoxysilane and continue stirring for 1.5 h, add 10 mL of 10 wt% ammonia water and stop stirring, transfer to a 60° C. water bath and let stand for 40 min, centrifuge, wash, and dry to obtain terminal double-bond organosilicon; Step B2, add 0.102 mol of allylamine and 0.1 mol of triethylamine into 200 mL of dichloromethane, slowly add 0.1 mol of dimethyl chlorophosphate at 5°C, and stir for 50 min, then heat to room temperature and stir for 10 h, filter, wash and dry, to obtain a functional monomer; Step B3, 0.02 mol of acrylic acid, 0.065 mol of functional monomer, and 0.03 mol of hydroxyethyl methacrylate are uniformly dispersed in 50 mL of ethanol, recorded as a mixed solution; 1.5 g of double-bonded silicone end is ultrasonically dispersed in 100 mL of ethanol, and then 50 mL of the mixed solution and 10 mL of azobisisobutyronitrile ethanol solution are added in sequence, and the temperature is raised to 60° C. to react for 4 hours, centrifuged, washed, and dried to obtain a macromolecular antistatic agent. The azobisisobutyronitrile ethanol solution is prepared by stirring and mixing azobisisobutyronitrile and ethanol in a dosage ratio of 0.13 g:10 mL. Example
[0015] The conductive filler is prepared by the following steps: Step A1, adding 0.1 mol / L 2-aminoterephthalic acid DMF (N, N-dimethylformamide) solution to a mixture of deionized water and ethanol and stirring for 10 min, then adding 0.075 mol / L copper nitrate DMF solution and 0.075 mol / L nickel nitrate DMF solution and mixing evenly, finally adding triethylamine and ultrasonicating for 2 h, centrifuging, collecting precipitates, washing, and drying to obtain CuNi-MOF powder, the volume ratio of 2-aminoterephthalic acid DMF solution, deionized water, ethanol, copper nitrate DMF solution, nickel nitrate DMF solution and triethylamine is 15:1:1:8:2:1.5; Step A2, dispersing 0.5 g of sodium molybdate in 50 mL of deionized water, adjusting the pH to 6.5, adding 60 mL of L-cysteine aqueous solution, ultrasonically treating for 20 min, hydrothermally reacting in an autoclave at 200 ° C for 24 h, centrifuging, collecting the supernatant, and obtaining MoS2 QDs. The L-cysteine aqueous solution is prepared by mixing L-cysteine and deionized water in a dosage ratio of 1.2 g: 60 mL; Step A3, after 0.2 g CuNi-MOF powder and 80 mL MoS2 QDs were mixed evenly, ultrasonic treatment was performed for 30 min, and then oil bath treatment was performed at 70°C for 8 h. After centrifugation, washing, and drying, calcination was performed at 400°C for 2 h to obtain a MoS2 QDs / CuNi-MOF composite material; Step A4, mix 2 mL of 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and 100 mL of deionized water, add 1.5 g of MoS2 QDs / CuNi-MOF composite material, ultrasonically disperse for 30 min, then heat to 30 ° C, add 0.45 g of dopamine hydrochloride, stir and react for 12 h, centrifuge, wash and dry to obtain a conductive filler.
[0016] The macromolecular antistatic agent is prepared by the following steps: Step B1, disperse 0.06 mol of tetraethyl orthosilicate and 0.04 mol of dimethyldiethoxysilane in a mixture of 100 mL of ethanol and 100 mL of deionized water, and stir for 2 h, then slowly add 0.03 mol of 3-butenetriethoxysilane and continue stirring for 2 h, add 10 mL of 10 wt% ammonia water and stop stirring, transfer to a 60° C. water bath and let stand for 50 min, centrifuge, wash, and dry to obtain terminal double-bond organosilicon; Step B2, add 0.153 mol of allylamine and 0.15 mol of triethylamine into 200 mL of dichloromethane, slowly add 0.15 mol of dimethyl chlorophosphate at 5°C, and stir for 60 min, then heat to room temperature and stir for 12 h, filter, wash and dry, i.e., obtain a functional monomer; Step B3, 0.03 mol of acrylic acid, 0.08 mol of functional monomer, and 0.04 mol of hydroxyethyl methacrylate are uniformly dispersed in 50 mL of ethanol, recorded as a mixed solution; 2 g of double-bonded silicone end is ultrasonically dispersed in 100 mL of ethanol, and then 50 mL of the mixed solution and 10 mL of azobisisobutyronitrile ethanol solution are added in sequence, and the temperature is raised to 65° C. to react for 5 hours, centrifuged, washed, and dried to obtain a macromolecular antistatic agent. The azobisisobutyronitrile ethanol solution is prepared by stirring and mixing azobisisobutyronitrile and ethanol in a dosage ratio of 0.15 g:10 mL. Example
[0017] A method for preparing an antistatic composition comprises the following steps: 30 parts of high-density polyethylene, 10 parts of linear low-density polyethylene, 5 parts of metallocene polyethylene, 0.5 parts of antioxidant 1010, 3 parts of dispersant (polyethylene wax), 1 part of lubricant (stearic acid), 8 parts of conductive filler prepared in Example 1, 3 parts of carbon black, 5 parts of macromolecular antistatic agent prepared in Example 1, 0.1 parts of initiator (diisopropylbenzene peroxide); Step S1, weighing raw materials by weight, adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, the conductive filler prepared in Example 1 and carbon black into a blender and mixing for 5 minutes, then adding antioxidant 1010, dispersant (polyethylene wax), lubricant (stearic acid), the macromolecular antistatic agent prepared in Example 1 and initiator (diisopropylbenzene peroxide) and continuing to mix for 10 minutes to obtain a mixture; Step S2, adding the mixed material into a twin-screw extruder, melt-blending at 190° C., extruding, and granulating to obtain an antistatic composition. Example
[0018] A method for preparing an antistatic composition comprises the following steps: 35 parts of high-density polyethylene, 15 parts of linear low-density polyethylene, 10 parts of metallocene polyethylene, 1 part of antioxidant 1010, 5 parts of dispersant (polyethylene wax), 2 parts of lubricant (stearic acid), 12 parts of conductive filler prepared in Example 2, 4 parts of carbon black, 8 parts of macromolecular antistatic agent prepared in Example 2, 0.3 parts of initiator (diisopropylbenzene peroxide); Step S1, weighing raw materials by weight, adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, the conductive filler prepared in Example 2 and carbon black into a blender and mixing for 10 minutes, then adding antioxidant 1010, dispersant (polyethylene wax), lubricant (stearic acid), the macromolecular antistatic agent prepared in Example 2 and initiator (diisopropylbenzene peroxide) and continuing to mix for 10 minutes to obtain a mixture; Step S2, adding the mixed material into a twin-screw extruder, melt-blending at 210° C., extruding, and granulating to obtain an antistatic composition. Example
[0019] A method for preparing an antistatic composition comprises the following steps: 40 parts of high-density polyethylene, 20 parts of linear low-density polyethylene, 15 parts of metallocene polyethylene, 3 parts of antioxidant 1010, 6 parts of dispersant (polyethylene wax), 3 parts of lubricant (stearic acid), 15 parts of conductive filler prepared in Example 3, 5 parts of carbon black, 10 parts of macromolecular antistatic agent prepared in Example 3, 0.5 parts of initiator (diisopropylbenzene peroxide); Step S1, weighing raw materials by weight, adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, the conductive filler prepared in Example 3 and carbon black into a blender and mixing for 10 minutes, then adding antioxidant 1010, dispersant (polyethylene wax), lubricant (stearic acid), the macromolecular antistatic agent prepared in Example 3 and initiator (diisopropylbenzene peroxide) and continuing to mix for 10 minutes to obtain a mixture; Step S2, adding the mixed material into a twin-screw extruder, melt-blending at 220° C., extruding, and granulating to obtain an antistatic composition.
[0020] Comparative Example 1 This comparative example is an antistatic composition, which differs from Example 6 in that graphite powder is used instead of the conductive filler prepared in Example 3, and the rest are the same.
[0021] Comparative Example 2 This comparative example is a type, and the difference from Example 6 is that the commercially available antistatic agent K-YD-C-3 type is used instead of the macromolecular antistatic agent prepared in Example 3, and the rest is the same.
[0022] The antistatic compositions prepared in Examples 4-6 and Comparative Examples 1-2 were compression molded to obtain samples, and the samples were subjected to performance tests: antistatic performance test: the surface resistivity of the sample was tested in accordance with GB / T1414; tensile yield stress test: the test was conducted in accordance with GB / T 1040; flexural modulus test: the test was conducted in accordance with GB / T9341-2000; The test results are shown in the following table:
[0023] It can be seen from the above table that after the surface resistivity test, the resistivity of the antistatic composition prepared by the present invention is 1.8×10 6 Ω-6.7×10 6 Ω range, indicating that it has excellent antistatic properties; after mechanical properties testing, the tensile yield stress is in the range of 59.4MPa-64.1MPa, and the bending modulus is in the range of 894MPa-923MPa, indicating that the comprehensive performance of the composition is also excellent.
[0024] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An antistatic composition, characterized in that The invention comprises the following raw materials in parts by weight: 30-40 parts of high-density polyethylene, 10-20 parts of linear low-density polyethylene, 5-15 parts of metallocene polyethylene, 0.5-3 parts of antioxidant, 3-6 parts of dispersant, 1-3 parts of lubricant, 8-15 parts of conductive filler, 3-5 parts of carbon black, 5-10 parts of macromolecular antistatic agent, and 0.1-0.5 parts of initiator; The conductive filler is prepared by the following steps: Step A1, adding 0.1 mol / L 2-aminoterephthalic acid DMF solution to a mixture of deionized water and ethanol and stirring for 10 min, then adding 0.075 mol / L copper nitrate DMF solution and 0.075 mol / L nickel nitrate DMF solution and mixing evenly, finally adding triethylamine and ultrasonicating for 1-2 h, centrifuging, collecting the precipitate, washing, and drying to obtain CuNi-MOF powder; Step A2, dispersing sodium molybdate in deionized water and adjusting the pH to 6.5, then adding L-cysteine aqueous solution for ultrasonic treatment for 10-20 minutes, hydrothermally reacting in an autoclave at 180-200°C for 24 hours, centrifuging, and collecting the supernatant to obtain MoS2 QDs; Step A3, after the CuNi-MOF powder and MoS2 QDs are evenly mixed, ultrasonic treatment is performed for 30 minutes, and then oil bath treatment is performed at 70°C for 5-8 hours. After centrifugation, washing and drying, calcination is performed at 300-400°C for 1-2 hours to obtain a MoS2 QDs / CuNi-MOF composite material; Step A4, mix 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and deionized water evenly, add the MoS2QDs / CuNi-MOF composite material, ultrasonically disperse it for 30 minutes, then heat it to 30°C, add dopamine hydrochloride, stir and react for 8-12 hours, centrifuge, wash and dry to obtain a conductive filler.
2. An antistatic composition according to claim 1, characterized in that: In step A1, the volume ratio of 2-aminoterephthalic acid DMF solution, deionized water, ethanol, copper nitrate DMF solution, nickel nitrate DMF solution and triethylamine is 15:1:1:5-8:2-5:1.
5.
3. An antistatic composition according to claim 1, characterized in that: In step A2, the dosage ratio of sodium molybdate, deionized water and L-cysteine aqueous solution is 0.2-0.5 g:50 mL:40-60 mL, and the L-cysteine aqueous solution is prepared by mixing L-cysteine and deionized water in a dosage ratio of 0.5-1.2 g:40-60 mL.
4. An antistatic composition according to claim 1, characterized in that: The usage ratio of CuNi-MOF powder and MoS2 QDs in step A3 is 0.1-0.2 g: 50-80 mL.
5. An antistatic composition according to claim 1, characterized in that: In step A4, the usage ratio of Tris-HCl buffer solution, deionized water, MoS2 QDs / CuNi-MOF composite material and dopamine hydrochloride is 1-2 mL: 100 mL: 0.5-1.5 g: 0.15-0.45 g.
6. An antistatic composition according to claim 1, characterized in that: The macromolecular antistatic agent is prepared by the following steps: Step B1, dispersing tetraethyl orthosilicate and dimethyldiethoxysilane in a mixture of ethanol and deionized water, and stirring for 1-2 hours, then slowly adding 3-butylenetriethoxysilane and continuing stirring for 1-2 hours, adding 10wt% ammonia water and stopping stirring, and transferring to a 60°C water bath and standing for 30-50 minutes, centrifuging, washing, and drying to obtain terminal double-bond organosilicon; Step B2, adding allylamine and triethylamine to dichloromethane, slowly adding dimethyl chlorophosphate at 0-5°C, and stirring for 40-60 minutes, then heating to room temperature and stirring for 8-12 hours, filtering, washing, and drying, that is, the functional monomer; Step B3, uniformly disperse acrylic acid, functional monomer and hydroxyethyl methacrylate in ethanol, record as mixed solution; ultrasonically disperse the double-bond end silicone in ethanol, then add the mixed solution and azobisisobutyronitrile ethanol solution in sequence, and heat to 55-65°C for reaction for 3-5h, centrifuge, wash and dry to obtain a macromolecular antistatic agent.
7. An antistatic composition according to claim 6, characterized in that: In step B1, the dosage ratio of tetraethyl orthosilicate, dimethyldiethoxysilane, ethanol, deionized water, 3-butenetriethoxysilane and ammonia water is 0.03-0.06 mol: 0.02-0.04 mol: 100 mL: 100 mL: 0.01-0.03 mol: 10 mL.
8. An antistatic composition according to claim 6, characterized in that: In step B2, the usage ratio of allylamine, triethylamine, dichloromethane and dimethyl chlorophosphate is 0.051-0.153 mol: 0.05-0.15 mol: 200 mL: 0.05-0.15 mol.
9. An antistatic composition according to claim 6, characterized in that: In step B3, the dosage ratio of the double-bond organosilicon, ethanol, the mixed solution and the azobisisobutyronitrile ethanol solution is 1-2g:100mL:50mL:10mL, the dosage ratio of acrylic acid, functional monomer, hydroxyethyl methacrylate and ethanol in the mixed solution is 0.01-0.03mol:0.05-0.08mol:0.02-0.04mol:50mL, and the azobisisobutyronitrile ethanol solution is prepared by stirring and mixing azobisisobutyronitrile and ethanol in a dosage ratio of 0.1-0.15g:10mL.
10. The method for preparing an antistatic composition according to claim 1, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, adding high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, conductive filler and carbon black into a blender and mixing for 5-10 minutes, then adding antioxidant 1010, dispersant, lubricant, macromolecular antistatic agent and initiator and continuing to mix for 10 minutes to obtain a mixture; Step S2, adding the mixed material into a twin-screw extruder, melt-blending at 190-220° C., extruding, and granulating to obtain an antistatic composition.